Harmoni Asuhan: Analisis Dampak Metode Parenting terhadap Pendidikan dan Perkembangan Anak dalam Islam dan Psikologi - Mahmudah, Nur; Azzahro, Siti Fatimah (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
Child as a blessing in Islam, requires the attention and responsibility of parents from the early stages of life. Islam teaches the importance of parental roles in partner selection, marriage preparation, and prenatal child education. Parents exert a significant influence on a child's development, shaping their moral awareness through socialization. The moral conduct of parents reflects Islamic values, emphasizing respect, honor, and compassion. Parental behavior plays a key role in shaping a child's character, impacting their overall development. Effective parenting, supported by both psychological theories and Islamic teachings, necessitates diverse skills, particularly responsiveness to the child and behavioral management. Research findings affirm that an effective parenting style, aligned with Islam, molds individuals who are confident, responsible, and possess strong self-regulation, reflecting a balance between Islamic principles and the developmental needs of children.